2015
DOI: 10.1103/physrevb.92.184432
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure of the antiferromagnetic half-Heusler compound NdBiPt

Abstract: READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/eng/copyright Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsAr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…For example, GdPtBi and NdPtBi exhibit magnetism arising from their 4f electrons preserving the Γ 8 -Γ 6 band inversion. The magnetic structures of these compounds are different: GdPtBi is a type-II antiferromagnet (18,19) whereas the magnetic structure of NdPtBi is of type I (20). Additionally, one should note that the magnetic moments and f-level fillings are distinct for neodymium and gadolinium and the exchange field is sufficiently large to reveal, for example, four pairs of Weyl points that appear in GdPtBi when B jj [111] (Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, GdPtBi and NdPtBi exhibit magnetism arising from their 4f electrons preserving the Γ 8 -Γ 6 band inversion. The magnetic structures of these compounds are different: GdPtBi is a type-II antiferromagnet (18,19) whereas the magnetic structure of NdPtBi is of type I (20). Additionally, one should note that the magnetic moments and f-level fillings are distinct for neodymium and gadolinium and the exchange field is sufficiently large to reveal, for example, four pairs of Weyl points that appear in GdPtBi when B jj [111] (Fig.…”
Section: Significancementioning
confidence: 99%
“…1A) so that along the [111] direction, the structure can be described as a metallic multilayer formed from successive atomic layers of rare earth, platinum, and bismuth. GdPtBi (18,19) as well as NdPtBi (20) are antiferromagnetic (AFM) metals at low temperatures below their corresponding Néel temperatures, T N = 9.0 and 2.1 K, respectively. The Gd spins order antiferromagnetically without any canting in zero magnetic field (as evidenced from μSR, discussed later) and saturate into a fully spin-aligned magnetic state in high magnetic fields at low temperatures [e.g., 25 T at 1.4 K ( Fig.…”
mentioning
confidence: 99%
“…Thus, it is clear that the Heusler name now refers to a broad and extensive family of compounds. Furthemore, all of these variants can be subjected to various structural distortions including a tetragonal elongation or compression along one of the cubic crystal axes, or a distortion along the [111] direction that leads to an hexagonal structure (9). Finally, superstructures are sometimes found that can arise from chemical ordering in non-stoichiometric compounds or from modulation of the structure and structural phase transitions, for example, in the case of shape memory alloys.…”
Section: Typementioning
confidence: 99%
“…Consequently, a connection between topological insulators, the zero gap-state, and thermoelectric performance is profound (87). [111] I [110] [111] I (a) [110] Weyl semimetals (WSM) are a class of topological semimetals, beyond topological insulators, where the conduction and valence bands cross in the vicinity of the Fermi level (88,89,90,91,92,93,94,95,96,97,98,99,100). The crossing points are called Weyl points that are separated in momentum space.…”
Section: Non-collinear Magnetic Structurementioning
confidence: 99%
“…Note that the peak splitting described above in three scenarios during the temperature evolution of the magnetic contribution to heat capacity is observed in real rare-earth antiferromagnets [7,[41][42][43][44][45][46][47][48] and actinide compounds [49], as well as a number of organometallic coordination polymers [50,51], molecular [52] and quasi-one-dimensional frustrated [53] magnets.…”
Section: Thermodynamics Of the System In The Frustration Regime Anmentioning
confidence: 77%